h-principles and flexibility in geometry - Geiges, Hansjörg, 1966- (Memoirs of the American Mathematical Society ; no. 779., 2003)
Introduction Differential relations and $h$-principles The $h$-principle for open, invariant relations Convex integration theory Bibliography.